(untitled) (Tạp chí Y học Cộng đồng, 2026)
Chronic hepatitis (CH) is a pathology caused by diverse etiologies and can progress to severe complications, including liver cirrhosis and hepatocellular carcinoma. It is also a major contributor to the global burden of disease and mortality, exerting a significant negative impact on the quality of life of millions of people worldwide. Over recent decades, this disease has received increasing scientific attention. Although conventional medicine has developed various pharmacological and non-pharmacological interventions, the currently available treatments still have certain limitations in efficacy associated with adverse effects. In this context, traditional medicine - with a rich diversity of herbal resources and a long-standing tradition - offers a promising therapeutic approach. A Vietnamese herbal formulation, "Misocholic tab", serves as a case study exemplifying the multi-targeted and synergistic principles of traditional medicine. This formulation contains multiple components with complementary pharmacological actions: Anti-inflammatory, hepatoprotective and choleretic effects (Extractum Fel Suillum, Extractum Cynarae Succus); antibacterial properties (Bulbus Allii Sativi) and antioxidant activity (Extractum Cynarae Succus, Bulbus Allii Sativi). This article emphasizes the growing trend toward developing standardized, evidence-based traditional medicinal formulations, which are considered a safe and effective approach to support the comprehensive management of liver diseases.